1994
DOI: 10.1007/bf00947973
|View full text |Cite
|
Sign up to set email alerts
|

Review of imaging techniques for the diagnosis of breast cancer: a new role of prone scintimammography using technetium-99m sestamibi

Abstract: Imaging techniques currently used for the diagnosis of breast cancer are reviewed and compared. Besides mammography, magnetic resonance imaging, positron emission tomography, and thallium-201 scintimammography, a new role of technetium-99m sestamibi scintimammography is discussed. It is concluded that while mammography remains the procedure of choice in screening asymptomatic women for breast cancer, other imaging methods play an important role in detecting malignancies in symptomatic patients. 99mTc-sestamibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1
7

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(56 citation statements)
references
References 28 publications
1
47
1
7
Order By: Relevance
“…It has been reported that 99m Tc-MIBI scintimammography is a highly sensitive test for the evaluation of breast masses and that it improves the specificity of conventional mammography by differentiating benign from malignant lesions. 99m Tc-MIBI breast imaging shows a sensitivity of 84%-96% for the detection of primary breast cancer [12,13,14,15,16,17,18]. In the present study, the rate of detection of breast cancer using 99m Tc-MIBI was within the range of these previous results.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…It has been reported that 99m Tc-MIBI scintimammography is a highly sensitive test for the evaluation of breast masses and that it improves the specificity of conventional mammography by differentiating benign from malignant lesions. 99m Tc-MIBI breast imaging shows a sensitivity of 84%-96% for the detection of primary breast cancer [12,13,14,15,16,17,18]. In the present study, the rate of detection of breast cancer using 99m Tc-MIBI was within the range of these previous results.…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, the rate of detection of breast cancer using 99m Tc-MIBI was within the range of these previous results. The value of imaging with patients in the prone position has been well established [13,14,16,17], in that it permits better separation of the deep breast structures from the high activity of myocardium and liver. In this study, nevertheless, patients were placed in an upright posterior oblique lateral position with the ipsilateral arm raised and with the face turned away from the side of the known breast lesion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, scintimammography was typically performed with the patient prone and with the camera positioned laterally, a technique pioneered by Khalkhali et al to improve separation of the breast from the chest and abdomen. 21,22 Even with this positioning, the distance between the gamma camera and the pendant, uncompressed breast during planar scintimammography was ∼5 cm. As the average thickness of the pendant breast is ∼16 cm, 23 a tumor in the middle of the breast could be 10-15 cm from the collimator face.…”
Section: Early Development Of Nuclear Breast Imagingmentioning
confidence: 99%